Retrospective study of the efficacy and safety of metronidazole and vancomycin for Clostridioides difficile infection. Issue 10 (October 2021) - Misawa, Kana; Iketani, Osamu; Enoki, Yuki; Taguchi, Kazuaki; Uno, Shunsuke; Uwamino, Yoshifumi; Hasegawa, Naoki; Matsumoto, Kazuaki
Abstract: Introduction: According to the Japanese guidelines for the management of Clostridioides difficile infection (CDI), the first choice is metronidazole (MNZ) for non-severe cases and vancomycin (VCM) for severe cases. However, the appropriateness of this first choice in Japanese patients is unclear. We therefore evaluated the appropriateness of the CDI management guidelines and the incidence of adverse drug reactions. Methods: The electronic chart data at Keio University Hospital between January 2012 and June 2019 were retrospectively reviewed. The response rate, the relapse rate, and the adverse reaction rate of treatment for CDI using MNZ or VCM were investigated according to the disease severity. Factorial analysis associated with the response, relapse, and adverse reaction was also performed. Results: In the 352 patients surveyed, no significant difference was observed in the response rate between MNZ and VCM regardless of the severity of CDI. The presence of cancer was a factor related to the persistence of diarrheal symptoms and older age was a risk factor for relapse. MNZ induced nausea significantly more frequently than VCM, and young age and female sex were risk factors for nausea. Conclusion: As no significant difference was observed in the response rate of CDI between MNZ and VCM, the Japanese CDI management guidelines, which recommend MNZ as the first choice, were demonstrated to be appropriate. Attention to nausea was also suggested to be necessary when administering MNZ to young females.